Rhetorical miraclesof Advancement and delay In the Holy Qur’an - BEHNAS, Chahrazed (Journal of Human Sciences, 2020)
The method of advancement in the syntax, Represents an essential element of the communication and the realization of its objectives, as well as the injury of the speaker’s purpose, in order to achieve communication between him and the interlocutor, and this is only for the purposes of rhetorical and methodological purposes. The Holy Qur’an is an inexhaustible source, a paradise whose fruits do not expire, but the fullness of hearing and sight remains with the heart and takes over the mind and conscience. In this art, as in others, it has reached the climax of the words that it deserves to express. And the method of advancement and delay, has a stylistic feature very influential in the knowledge of the properties of the structures of speech, and reveals the secrets of oneself, and drowns in its depths, and portray the characters of the scene in the form of the presence of showing the joy or pleasure or disorder or tension or faith or hypocrisy or other... He was able to address the heart and the Conscience at the same time, with its high meanings and literature, which activate the imagination and move the mind, it has the ability to carry the listener or reader to participate in activating the Quranic position. And the words of the Qur’an are significant in the context of the sentence, if we look at the significance of the word chosen under their advancement, this led to highlight the meaning of strength and clarity, and helped to portray the scene in the flow and life. And the miracles of the method of advancement and delay, is an excess Miracle, cannot be restrict.. And his role in the verses of the judgments, is not less of his role in the scenes of the Hereafter, and the way to expose their flood and touch their secrets and connotations, remains a context mellowleafy of fruits and flowers..